Теоретичні аспекти фінансового планування на державних підприємствах - Бровко, Лариса Іванівна; Brovko, L.; Пасечник, О. В.; Pasechnyk, O. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
Статтю присвячено дослідженню системи фінансового планування в Україні та процедурі формування фінансових планів державними підприємствами, оскільки в сучасних умовах господарювання поряд з підприємствами, заснованими на приватній власності, існує ще досить велика кількість унітарних підприємств та господарських товариств, у статутному капіталі яких більше 50 відсотків акцій (часток) належать державі. У статті розглянуто існуючий порядок складання фінансових планів державними підприємствами та звітів про їх виконання, як основного елементу контролю за діяльністю таких підприємств з боку держави. Проаналізовано алгоритм побудови фінансових планів, їх класифікацію, а також основні складові фінансового плану державних підприємств. Досліджено та виявлено низку проблем, які виникають у процесі організації фінансового планування на державних підприємствах, та вирішення яких забезпечить стійкий розвиток підприємств у сучасних умовах господарювання, а також сприятиме збалансуванню фінансів реального сектору економіки. The article is devoted to the study of the system of financial planning in Ukraine and the procedure of formation of financial plans by state-owned enterprises, since in the current conditions of management, there are still quite a large number of unitary enterprises and economic entities in the authorized capital of which more than 50 percent of shares (parts) are state-owned. State ownership is undoubtedly characterized by a high level of concentration of production, which makes it possible to use the effect of the scale of production. State property provides an opportunity to concentrate resources on the decisive areas of production, to promote the development of basic industries, in addition, it forms the basis for central planning and management of the national economy. Financing of economic activity of state-owned enterprises occurs both at the expense of the State Budget of Ukraine and at the expense of own or borrowed funds, which requires effective control not only by the enterprise itself but also by the state, so for state-owned enterprises the planning function is traditional. But in a market environment, the requirements for quality planning become more stringent, as it must not only ensure the production of competitive products and profitable activity alongside commercial entities but also make it impossible to bankrupt and liquidate state-owned enterprises. The article examines the existing procedure for drawing up financial plans by state-owned enterprises and reports on their implementation, as the main element of control over the activity of such enterprises by the state. The algorithm of construction of financial plans, their classification, as well as the main components of the financial plan of state-owned enterprises was analyzed. Despite the fact that the process of organizing financial planning in state-owned enterprises is sufficiently regulated at the legislative level, it has some its disadvantages. Yes, it is characterized by unreality, inactivity, incomprehensibility of indicators for management, inconsistency between long-term and short-term plans, the unreasonableness of indicators, the lack of a comprehensive approach to their preparation, as well as the uncontrolled implementation of plans, so the implementation of effective planning, methodological and organizational support both at the state and enterprise-level will contribute to the increased profitability of enterprises and their competitiveness, increase of revenues to the state and local budgets. This will ensure the sustainable development of enterprises in the current economic environment and will help to balance the finances of the real sector of the economy.
Theoretical aspects of financial planning at state-owned enterprises
Л. І. Бровко ORCID ID: 0000B0003B2577B0741 ; О. В. Пасечник ORCID ID: 0000B0001B9335B9773
Keywords: фінансове планування; financial planning; фінансовий план; financial plan; звіт про виконання фінансового плану; financial plan implementation report; державні підприємства; state-owned enterprises; бюджетування; budgeting